(untitled) (Journal of Special Education and Rehabilitation, 2014)
The Master’s thesis is presented on 149 pages. The paper contains the following sections: Introduction, Theoretical approach to the problem of the research, Research section which contains: Research methodology, Analysis and interpretation of the results, Discussion, Conclusions, Recommendations, Articles and Literature. The Introduction explains the concept of behavioral disorder and the different sets of risk factors that lead to the appearance of behavioral disorder. Commonly, we distinguish two main groups of etiological factors that lead to behavioral disorder: environmental factors and factors related to the person’s functioning. In the recent decades, the number of children with behavioral disorders is increasing more and more, and this increase entails the need for timely identification of the risk and the protective factors, which means that prevention and early intervention, as a permanent and active process, must begin as early as possible, and the best moment is in the preschool period.The Theoretical basis gives definition of the term behavioral disorder from several aspects (legal, medical, special-educational and empirical), mentions different terminology which is used in scientific literature, as well as data for the prevalence, comorbidity and various classification systems, within which the behavioral disorder is covered. Also, the risk factors that lead to behavioral disorder, divided into several groups: individual factors, family factors, factors related to school, peers and factors related to the social environment are elaborated. Besides the risk factors, the factors for protection and their division are elaborated too. An important part of the theoretical basis takes the definition for prevention and early intervention, including the types of prevention and the models of early intervention that are commonly used in working with students with behavioral disorder. The Research section presents the methodology of the research and defines the subject, the purpose and the character of the research, the goals, the hypothesis, the variables, the methods, the techniques and instruments, the sample, the statistical data processing, the place, the time, the organization and the course of the research. The underlying purpose of this research is to determine the risk factors for the emergence of behavioral disorder among students from primary schools and also the need for taking some measures for prevention and early intervention. The sample of the research consisted of 70 teachers and class teachers from five primary schools in Prilep that have students with behavioral disorder in their classes. They are divided in two groups: 35 teachers and class teachers are from schools in the urban community and the rest 35 are from schools in the rural community. The methodological structure is based on the descriptive method and the method of comparative analysis. The analysis of documentation, survey and scaling were used as techniques. For data collecting two types of questionnaires were used: Questionnaire for teachers/class teachers and The Strengths and Difficulties Questionnaire. The collected data was grouped, tabled and graphically displayed and the distribution of frequency, ponder arithmetic mean and χ2 was calculated using PSPP for Windows 7 (for the statistically significant difference we used the difference that has a significance level of p < 0.05). The Analysis and interpretation of the results shows that the risk factors for the emergence of behavioral disorder among students from primary schools are associated with the individual characteristics of the student, the family, the school and the peers’ influence. The verification of the hypothesis gives the following conclusions: the behavioral disorder is more prevalent among boys than girls (81.42%); in most of the cases (41.42%) the behavioral disorder appears between the age of 9 - 12 years; 60 % of the students with behavioral disorder live in families with low material incomes; 50% of the students with behavioral disorder are in company only with friends who also have behavior problems. The fact that most of the students with behavioral disorder (54.28%) have an intense need for intervention is worrying. Based on the results and the conclusions we can give the following recommendations (social-protective, medical, educational and legal): timely recognition and detection of behavioral disorder, identification of the risk factors and the strengthening factors for protection; planning, development and implementation of programs for prevention and early intervention of the behavioral disorder locally and nationally; organization of the free time of these students; promotion of the cooperation between school, family, the Center for social work and the local community.